The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1556/2060.104.2017.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the enteric nervous system in the control of the migrating motility complex

Abstract: The migrating motility complex (MMC), a cyclical phenomenon, represents rudimentary motility pattern in the gastrointestinal tract. The MMC is observed mostly in the stomach and gut of man and numerous animal species. It contains three or four phases, while its phase III is the most characteristic. The mechanisms controlling the pattern are unclear in part, although the neural control of the MMC seems crucial. The main goal of this article was to discuss the importance of intrinsic innervation of the gastroint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 280 publications
1
1
0
Order By: Relevance
“…50 Romanski et al also indicated that Gas-mediated binding of the cholecystokinin receptor could stimulate gastrointestinal motility by acting on smooth muscles, and SS located in the interneurons of the submucosal and myenteric plexuses throughout the digestive tube could block the release of MTL and inhibit the motility of the intestinal tract. 51 In our study, L. fermentum XJ61, CECT5716, and YN54 alleviated the decrease in Gas in the intestinal tract of constipated mice to varying degrees, and only L. fermentum YN54 regulated both SS and VIP (Fig. 4).…”
Section: Food and Function Papersupporting
confidence: 51%
“…50 Romanski et al also indicated that Gas-mediated binding of the cholecystokinin receptor could stimulate gastrointestinal motility by acting on smooth muscles, and SS located in the interneurons of the submucosal and myenteric plexuses throughout the digestive tube could block the release of MTL and inhibit the motility of the intestinal tract. 51 In our study, L. fermentum XJ61, CECT5716, and YN54 alleviated the decrease in Gas in the intestinal tract of constipated mice to varying degrees, and only L. fermentum YN54 regulated both SS and VIP (Fig. 4).…”
Section: Food and Function Papersupporting
confidence: 51%
“…21,32 Many naturally occurring peptide modulators control the MMC in the enteric nervous system, and among them the opioid receptor-dependent influences were the most significant. [33][34][35] Trimebutine also acts through the release of GI peptides such as motilin, vasoactive intestinal peptide, gastrin and glucagon. 21 Motilin and other compounds involving motilin receptors appeared to play a significant role in the initiation of phase III of the MMC in man and dogs, but not in pigs.…”
Section: Discussionmentioning
confidence: 99%